(untitled) (Development Service Industry Management, 2025)
The purpose of the article is to analyze the quality of service provision and study the possibility of their improvement, as one of the main factors of service activity and competitiveness of hotel and restaurant business establishments. The article analyzes the features of service quality in hotel and restaurant facilities and provides definitions of the concept of quality by various researchers. The essence of the quality of products and services is characterized, the analysis of basic and additional services in the hotel and restaurant industry is carried out. An analysis of research by scientists on the quality of food and accommodation services is carried out. Trends in the development of restaurant services are researched. The quality of hotel and restaurant services is a leading component of the entire quality service system. It encourages guests to choose a particular product in certain market segments and influences the guest’s decision to use the services of a particular hotel/restaurant rather than a competitor. When providing services, the success of the hotel and restaurant industry depends on the quality of the services provided, the degree of guest satisfaction and their safety, as deterioration in quality leads to the loss of service consumers. High quality of service can be achieved through staff training, and therefore, the management of hospitality enterprises should pay attention to the development and implementation of a system of internal training and staff training. Consistently high quality of service in the hospitality industry is achieved through training and motivation of staff. Increasing employee motivation will improve service activities, quality of service, and the level of quality services provided in hotel and restaurant establishments.